Quilombola women from Jequitinhonha (Minas Gerais, Brazil) and access to water and sanitation in the context of COVID-19: a matter of human rights - Neves-Silva, Priscila; Schall, Brunah; Gonçalvez, Flora Rodrigues; Alves, Estela Macedo; dos Santos, Sebastiana Rodrigues; Valente, Polyana Aparecida; Pimenta, Denise Nacif; Heller, Léo (Frontiers in Water, 2024)
IntroductionIn Brazil there are currently 3,475 certified quilombo communities, reminiscent of Black communities founded by African enslaved people. In the Jequitinhonha Valley, a semi-arid region located in northeastern Minas Gerais State, Brazil, there are approximately 80 established communities, mostly in hard-to-reach areas with lack of access to water and sanitation services.MethodsUsing the analytical framework of Human Rights to Water and Sanitation (HRWS) and with a gender perspective, this research aimed to analyze how access to water and sanitation occurs in two remaining communities of quilombos (Córrego do Narciso and Córrego do Rocha) located in the Jequitinhonha Valley and how lack of access to these services impacts the health and lifestyle of the population, especially during the COVID-19 pandemic. The study used qualitative methods. Data was collected using individual interviews and focus groups. The data was analyzed using content analyses technique.ResultsThe results showed that access to water and sanitation in both communities did not respect the HRWS normative content and the lack of access impacted the lifestyle—the economic, cultural and social traditional activities-and the health of the population, especially for women. During COVID-9 pandemic access to water became even more difficult because the supply by water truck was discontinued producing more insecurity as people in the communities, especially women, needed to go to the city to buy water and food and could not keep isolation.DiscussionPublic policies on access to water for rural populations, especially quilombolas, if guided by the HRWS framework and interwoven with the gender perspective, could ensure guaranteed quality of life for women and can strength their entitlements within their territories.